MODERN CHALLENGES IN GOVERNMENTAL REGULATION OF LABOUR FORCE MIGRATION IN UKRAINE - Chernyak, Oleksandr; Chernyak, Yevgen (Ekonomika, 2012)
The work includes an analysis of the main modern challenges in the sphere of the labour force migration in Ukraine. The development of governmental regulations of labour force migration will give Ukraine a chance to improve the quality of workforce coming from abroad and to avoid the quitting of scientists by making them able to be employed in Ukraine. Also, changes in migration policy will help to decrease the unemployment rate in the country. The influence of labor force migration on the country’s economic development is also measured. The necessity of changes in governmental regulation of labor force migration in Ukraine is described in the paper. The government should make several steps to stimulate the usage of local labor force instead of cheap and unqualified foreigners by national enterprises. The first step is to provide the “quality rate” of a foreigner to be employed. The second step is the governmental support of enterprises that will act according to the mentioned rules and carefully regard the professionalism of employees. Such enterprises should receive subsidies.